Reconstruction of environmental change and sedimentation processes during the Pleniglacial using fluvio-lacustrine sediments from volcanically-dammed Paleolake Alf, West Eifel Volcanic Field, Germany - Eichhorn, Luise (2017)
This study focuses on a fluvio-lacustrine sediment archive from Paleolake Alf (33-13.8 cal. ka BP) in the West Eifel Volcanic Field, Germany. It formed due to volcanic eruptions of the Wartgesberg Volcano Complex that blocked the Alf River with scoria and lava and created a dammed lake. In the Alf Valley, this volcanic dam trapped the Middle to Late Pleniglacial sediments. Main objective of this study was to improve the understanding of the paleoenvironmental change during the Middle and Late Pleniglacial including transport media, deposition structure and denudation rate. Specifically, sediment transport/ deposition processes in the Alf catchment and lake were reconstructed in combination with a design of the lake basin architecture. Further, the trapped sediment volume in the lake was calculated by applying a multidisciplinary approach combining field surveys, sedimentological, geophysical and GIS-based investigations. According to reconstructions of this study, Paleolake Alf had a maximum lake level of 410 m a.s.l. and a catchment area of ~ 55 km. Sediment core investigations from the bottomset area of the lake basin revealed (sub)millimeter (Unit I) to millimeter (Unit II) thick light and dark laminae. Light, clayey silt laminae formed during winter when Paleolake Alf was ice-covered, indicated by dropstones. Dark, silt-sized laminae were subdivided into Type I: Laminae with normal grading, and Type II: Laminae with graded sublayers. The calculated lacustrine sediment volume amounts to 25 Mio. m equalling a Pleniglacial denudation rate of 37.5 mm · ka-1 between 33 and 21 cal. ka BP. This value is in the same order of magnitude as the calculated denudation rate from the Allier River basin in French Massif Central between 29 and 16 ka BP. By correlating the Paleolake Alf record with the NGRIP ice core, the slight grainsize coarsening and the calcium increase in the lacustrine sediments (Unit II) could be explained with a change from Interstadial to Stadial ~ 26.3 ka BP.